Money tales: Aisyah, Adam and friends - Sabri, Mohamad Fazli; Ramli, Nurhayatul Nira (Universiti Putra Malaysia Press, 2019)
This book Money Tales of Aisyah, Adam and Friends is written specifically for the parent, teacher and educator to be made into teaching and learning materials both in and outside the classroom, also as a guide to educate the children and student about planning and financial management skills. It is also suitable as light reading for children and student in their spare time. In addition, this book also provides 30 tips that can be a guide for parents, teachers and educator to educate children and students to become planner and financial managers who are smart and prudent. The tips provided are suitable for practice in daily life.